Polybenzoxazine Aerogels for Thermal Protection at Extremely High-Temperature/Cryogenic Conditions. (18th November 2022) - Zhang, Sizhao; Wang, Jing; Lu, Kunming; Xu, Guangyu; Wang, Zhao; Xiao, Yunyun; Ji, Hui; Yang, Zhouyuan; Yang, Yue; Xiong, Shixian; Li, Zhengquan
Abstract: Polybenzoxazine (PBZ) aerogels are potential thermal insulation and ablative material for thermal protection system in aerospace. However, obtaining the excellent properties of thermal insulation and compression strength remain a formidable challenge at an extreme temperature. Here we proposed a new strategy by optimizing the nanoporous networking structure and pore size distribution to prepare PBZ aerogel (PAs-Fx), which could be self-extinguished in 0.24 s only once departing the outer flame, and the compressive stress of PAs–F10 reached up to 6.62 MPa at the strain of 10%. PAs–F10 presented great advantage in thermal insulation property (although the hot surface existed in the atmosphere at 302.4 °C, the temperature of cold surface remained at only 112.4 °C when heat flow was stable). Even burning the hot surface with 1200 °C outer flames for 30 min, the highest temperature of the cold surface only reached 254 °C at the heat balance state, moreover, the prominent shape-keeping property was confirmed after ultra-high temperature burning. We also found that PAs–F10 has superior compressive strengths which are 5.52 and 9.38 MPa at 10% strain in the conditions of ambient temperatures for 150 and −50 °C, respectively. PAs-Fx could also retain the excellent compression property after treating cryogenically in liquid nitrogen (−196 °C). The work would be a great promise in the application of ablative thermal insulation materials in a great measure in the future. Graphical abstract: Image 1 Highlights: The PAs-Fx aerogels behave abundant nanoporous networking structure, good thermal insulation properties, flame retardancy feature. PAs–F10 behave excellent thermal insulation property in extreme high temperature environment (1200 °C). This is the first report on the compression properties of PBZ aerogels in extreme environments (150 and −50 °C). PAs-Fx aerogels could also retain the excellent compression property after treating cryogenically in liquid nitrogen (−196 °C).